Rāingān samrūat kh̨ōmūn ph̄ưnthān r̨ōp thī 1 (2543) = Report of baseline survey round 1 (2000) (IPSR publication ;, 2001)
Report on population survey in Kanchanaburi Province, Thailand; includes statistics.